Impact of climate‐driven temperature increase on inland aquaculture: Application to land‐based production of common carp (Cyprinus carpio L.). Issue 5 (10th May 2022) - Panicz, Remigiusz; Całka, Beata; Cubillo, Alhambra; Ferreira, João G.; Guilder, James; Kay, Susan; Kennerley, Adam; Lopes, André; Lencart e Silva, João; Taylor, Nick; Eljasik, Piotr; Sadowski, Jacek; et al.
Abstract: Climate change will expose the food‐producing sector to a range of challenges. Inland aquaculture farms are particularly vulnerable, due to the difficulty in changing their location, and therefore require specific tools to predict the influence of direct and indirect effects on production, environment and economic feasibility. The objective of our study was to apply a simple set of models to produce a set of growth, risk and suitability maps for stakeholders within the common carp sector in Poland, to assist decision‐making under two different scenarios of climate change: a moderate situation (RCP 4.5) and an extreme situation (RCP 8.5). We used present (2000–2019) and future projections (2080–2099) for water surface temperature based on land surface temperature data from regionally downscaled climate models to draw maps to: (i) show optimal temperature conditions for carp growth, (ii) assess risk of disease outbreak caused by three important common carp pathogens: Cyprinid herpesvirus 3 (CyHV‐3), carp oedema virus (CEV) and spring viremia of carp (SVCV) and (iii) predict potential suitability changes of carp farming in Poland. The study identified areas with the most and least favourable temperature conditions for carp growth, as well as those areas with the highest/lowest number of days with suitable temperatures for virus infection. These suitability maps showed the combined effect of direct and indirect effects of climate change projections under RCP 8.5 and RCP 4.5 scenarios. The approach applied herein will be of use worldwide for analysing the risks of temperature increase to land‐based aquaculture, and the results presented are important for carp farmers in Poland and elsewhere, industry in general, and government stakeholders, to understand the direct and indirect effects of climate change on the triple bottom line of people, planet, and profit.